Research And Statistical Analysis On Vegetable Production And Trade - Dalila G. STOICA; Veronica T. BACIU; Mirela STOIAN; Marian MOTOFEANU; Cristina M. STERIE (Communications of International Proceedings, 2021)
Ensuring human health requires a balanced consumption of agri-food products, in which legumes and fruits have an important place. Vegetables are complex foods that contain many nutrients and vitamins essential for the proper and normal development of people. The paper analyzes the trends of vegetable production, consumption and trade in Romania. With regard to the consumption of vegetables, it is important to establish the link between the production obtained and their consumption. The aim of the paper is to investigate the connection between the two variables by applying statistical analysis methods using SPSS, the simple linear regression model. Romania is a country that is based on imports, and has exported goods 5 times less in value, 95.3 million euros. The analysis resulted in a correlation coefficient ( ) of 46% which indicates average link between, consumption and vegetable production.
Keywords: Vegetable; Romania; Production; Trade.